Subjective interactions in education - Barbara Wojciechowska-Charlak; Teresa Zubrzycka-Maciąg (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Abstract: As a human attribute, subjectivity may also be a feature of social relations. In this meaning, subjectivity plays a particular role in the educational interaction, as it controls the nature of the mutual relations among the individuals involved in the educational process. The aim of this article is to illustrate the nature and determinant qualities of subjective interaction in education. Presented here are internal and external factors of subjectivity. The role of the student and the teacher in the building of double-subjective relationship is also discussed. Moreover, the article demonstrates the possibilities of experiencing and developing the subjectivit of the persons participating in the process of education.